Travel, pilgrimage and social interaction from antiquity to the Middle Ages
1 online resource (x, 318 pages).
Keywords: Mobility and travel have always been key characteristics of human societies, having various cultural, social and religious aims and purposes. Travels shaped religions and societies and were a way for people to understand themselves, this world and the transcendent. This book analyses travelling in its social context in ancient and medieval societies. Why did people travel, how did they travel and what kind of communal networks and negotiations were inherent in their travels? Travel was not only the privilege of the wealthy or the male, but people from all social groups, genders and physical abilities travelled. Their reasons to travel varied from profane to sacred, but often these two were intermingled in the reasons for travelling. The chapters cover a long chronology from Antiquity to the end of the Middle Ages, offering the reader insights into the developments and continuities of travel and pilgrimage as a phenomenon of vital importance.